2020
DOI: 10.1101/2020.01.21.914341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prepronociceptin expressing neurons in the extended amygdala encode and promote rapid arousal responses to motivationally salient stimuli

Abstract: Motivational states are complex and consist of cognitive, emotional, and physiological components controlled by a network across multiple brain regions. An integral component of this neural circuitry is the bed nucleus of the stria terminalis (BNST). Here, we identified a subpopulation of neurons within BNST expressing the gene prepronociceptin (Pnoc BNST ), that can modulate the rapid changes in physiological arousal that occur upon exposure to stimuli with motivational salience. Using in vivo two-photon calc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
(96 reference statements)
1
3
0
Order By: Relevance
“…Considering that salience is an important predictor of pain sensitivity and analgesic efficacy (Borsook et al, 2013), it is possible that alterations in the timing and synchrony of BNST CRF+ responses will change nociceptive detection and contribute to pain sensitivity in a sex-specific manner. This is an intriguing possibility given that BNST neurons expressing Crf or the prepronociceptin gene have been reported to exhibit in vivo responses to motivationally salient and aversive stimuli such as predator odor (Giardino et al, 2018;Rodriguez-Romaguera et al, 2020). These observations support prior conclusions that the BNST encodes for salient threats that may cause physical or emotional harm (Somerville et al, 2010;Borsook et al, 2013;Grupe et al, 2013;Avery et al, 2016;Hermann et al, 2016;Minami, 2019).…”
Section: Bnst Crf+ Neurons Dynamically Respond To Noxious Heat Acrosssupporting
confidence: 59%
“…Considering that salience is an important predictor of pain sensitivity and analgesic efficacy (Borsook et al, 2013), it is possible that alterations in the timing and synchrony of BNST CRF+ responses will change nociceptive detection and contribute to pain sensitivity in a sex-specific manner. This is an intriguing possibility given that BNST neurons expressing Crf or the prepronociceptin gene have been reported to exhibit in vivo responses to motivationally salient and aversive stimuli such as predator odor (Giardino et al, 2018;Rodriguez-Romaguera et al, 2020). These observations support prior conclusions that the BNST encodes for salient threats that may cause physical or emotional harm (Somerville et al, 2010;Borsook et al, 2013;Grupe et al, 2013;Avery et al, 2016;Hermann et al, 2016;Minami, 2019).…”
Section: Bnst Crf+ Neurons Dynamically Respond To Noxious Heat Acrosssupporting
confidence: 59%
“…The vast majority of BNST neurons release the inhibitory neurotransmitter GABA, form symmetric synapses, and express the vesicular GABA transporter (vGAT) (Kudo et al, 2012;Mazzone et al, 2018;Moffitt et al, 2018;Welch et al, 2019;Rodriguez-Romaguera et al, 2020). Thus, BNST outputs generally inhibit their target cells.…”
Section: Neurochemical Architecturementioning
confidence: 99%
“…For example, one recent study that performed single-cell transcriptional profiling of BNST neurons reported that they can be divided into as many as 41 different transcriptional clusters (Welch et al, 2019). Another study suggested that BNST neurons can be divided into 11 distinct transcriptional clusters, and that expression of pre-pro-nociceptin, the precursor for the NC neuropeptide, is distributed across 4 of these 11 clusters (Rodriguez-Romaguera et al, 2020). These two studies likely identified differing numbers of BNST cell types because of the clustering analyses used.…”
Section: Neurochemical Architecturementioning
confidence: 99%
See 1 more Smart Citation